Staphylococcus aureus Infections in the Paediatric Intensive Care Unit: Illustrated Cases - Kam Lun Hon; Ronald C. M. Fung; Karen K. Y. Leung; Alexander K.C. Leung; Wun Fung Hui; Wing Lum Cheung (Case Reports in Pediatrics)
Staphylococcus aureus is known to be one of the most common gram-positive microorganisms and an important pathogen associated with sepsis and toxic shock. We present four anonymized consecutive cases in a paediatric intensive care unit (PICU) to illustrate the different clinical manifestations of staphylococcal infections, including local infection versus systemic infection, toxic shock versus septic shock, and osteomyelitis. Eczema, short gut syndrome, and scald injury may be associated. Haematologic and coagulopathic abnormalities may be present. Prompt diagnosis and use of appropriate antimicrobial treatments is essential to reducing mortality and morbidity associated with staphylococcal infections.